Montessori's Perspective on Citizenship Education - Jaap de Brouwer; Lida Klaver; Symen van der Zee (University of Kansas, 2023)
The purpose of this study is to synthesize Montessori's writings on citizenship education to support the implementation of a Montessorian view. This synthesis demonstrates that Montessori was of the explicit conviction that a better world can be achieved through citizenship education, as it strives for a peaceful and harmonious society. We approach this topic through the Dutch context. Although schools in the Netherlands are required by law to promote active citizenship and social cohesion, this law does not stipulate which of the many different views on citizenship education schools must adhere to. Schools have the liberty to devise their own citizenship curricula if they can substantiate their views and choices. For Montessori schools, this requires insight into Montessori's view on citizenship education. Although Montessori's views are still largely appropriate in our time, an ongoing dialogue about citizenship education is required, as Montessori lived and worked in a specific geopolitical context. Based on our analysis, we have identified seven themes that characterize Montessori's view on citizenship education: one common citizenship goal; preparation for independent thinking and action; image of the future citizen; adapted and critical citizens; humanity for harmony; knowledge as prerequisite, personality development as goal; and an ever-expanding worldview. The results of this study provide valuable insights for designing and teaching citizenship education through a Montessorian lens.